Network toxicological insights into DEHP exposure and thyroid cancer development and progression - Zhang, Yuhang; Wang, Qiang (Frontiers in Oncology, 2025)
This study aimed to identify markers of di-2-ethylhexyl phthalate (DEHP) exposure associated with thyroid cancer occurrence and prognosis by integrating network toxicology and molecular docking. Expression profiles and clinical information were obtained from TCGA-THCA and five GEO datasets (GSE3467, GSE3678, GSE33630, GSE53157, and GSE60542). Venn diagram analysis revealed six overlapping genes (CYP1B1, ABCC3, KRT19, CUX2, GABRB2, and TNFSF15) between the combined dataset and DEHP’s target genes. GO and KEGG enrichment analyses were conducted on these overlapping genes. Through multivariate COX regression model, it is clearly seen that CYP1B1, GABRB2 and TNFSF15 are highly expressed, and can basically be determined as candidate hub genes. Kaplan-Meier survival analysis indicated that the high-risk group had a significantly poorer prognosis (p < 0.05). Furthermore, prognostic ROC curves based on the GEO validation set demonstrated that CYP1B1, GABRB2, and TNFSF15 were significantly associated with thyroid cancer diagnosis (AUC exceeding 0.86). Finally, molecular docking was employed to visualize the interaction sites between DEHP and its target genes. In conclusion, this study provides novel targets for the prevention and treatment of thyroid cancer in the context of DEHP exposure.